Interparental conflict and emerging adults’ romantic relationships: The role of emotional dysregulation and relationship commitment - Matoso, Mariana Baeta (2021)
The interparental relationship provides a model for offspring’s relationships, and research has shown that destructive interparental conflict has negative implications for emerging adults’ romantic relationships. Specifically, studies in this area have shown harmful effects of interparental conflict on emerging adults’ emotional regulation skills and relationship commitment, as well as on their satisfaction with, and the quality of, their romantic relationships. However, little is known about the role of relational commitment and emotional regulation skills in the relationship between exposure to interparental conflict and the satisfaction and quality of these relationships. To address this gap in the literature, the present study investigated the mediating role of emotional dysregulation and relationship commitment in the association between exposure to destructive interparental conflict and emerging adults’ romantic relationship quality and satisfaction. Participants were 425 emerging adults, aged 18 and 25 years old, who were, or had been in the past 6 months, in a romantic relationship. Supporting our hypothesis, results revealed that exposure to destructive interparental conflict was associated with less satisfaction and worse relationship quality through greater emotional dysregulation and less commitment to the relationship. This study supports previous research by reinforcing the role of interparental conflict as a predictor of emerging adults’ difficulties in their romantic relationships and highlights the importance of emotional regulation skills and commitment to the relationship as explaining mechanisms of that association, thus providing important implications for practice.